The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1152/jappl.2001.90.1.380
|View full text |Cite
|
Sign up to set email alerts
|

Selected Contribution: Mechanisms underlying increased force generation by rat diaphragm muscle fibers during development

Abstract: It has been found that maximum specific force (F(max); force per cross-sectional area) of rat diaphragm muscle doubles from birth to 84 days (adult). We hypothesize that this developmental change in F(max) reflects an increase in myosin heavy chain (MHC) content per half-sarcomere (an estimate of the number of cross bridges in parallel) and/or a greater force per cross bridge in fibers expressing fast MHC isoforms compared with slow and neonatal MHC isoforms (MHC(slow) and MHC(neo), respectively). Single Trito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
79
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 44 publications
4
79
0
Order By: Relevance
“…It was not possible, however, to design reliable primer pairs for the MHC 2B isoform suitable for real-time RT-PCR using a mimic internal control. This isoform is usually expressed at low levels and rarely is singly expressed (15,37), and thus it is unlikely to produce a measurable impact on conclusions regarding MHC transitions during postnatal development. To document any relative change in MHC 2B mRNA expression across developmental time points, Northern blot analyses of MHC 2B mRNA were conducted, as previously described (13).…”
Section: Mhc Isoform Mrna Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was not possible, however, to design reliable primer pairs for the MHC 2B isoform suitable for real-time RT-PCR using a mimic internal control. This isoform is usually expressed at low levels and rarely is singly expressed (15,37), and thus it is unlikely to produce a measurable impact on conclusions regarding MHC transitions during postnatal development. To document any relative change in MHC 2B mRNA expression across developmental time points, Northern blot analyses of MHC 2B mRNA were conducted, as previously described (13).…”
Section: Mhc Isoform Mrna Expressionmentioning
confidence: 99%
“…However, during postnatal development of the rat Dia m , MHC content (measured by MHC mass per half-sarcomere volume and fiber cross-sectional area) increases markedly (15). This increase varies across fiber types (classified based on MHC isoform expression).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain, at least in part, the slower maximum shortening velocity of the rat Dia m during early postnatal development, when MHC Neo and MHC Slow contribute predominantly to the MHC isoform composition of the muscle (16,27,29,30,35). The lower maximum specific force (force normalized for fiber cross-sectional area) and greater fatigue resistance of the neonatal Dia m may also be partially explained by the predominant expression of MHC Neo and MHC Slow isoforms (10,16,29,33,35).In previous studies (14, 27, 31), our laboratory employed a quantitative histochemical procedure to determine the maximum velocity of the actomyosin ATPase reaction (V max ATPase) in muscle fibers expressing different MHC isoforms. In the rat Dia m , we found that fibers expressing MHC 2X and MHC 2B isoforms display significantly higher V max ATPase compared with fibers expressing MHC Slow and MHC 2A isoforms.…”
mentioning
confidence: 98%
“…In adult skeletal muscle, several MHC isoforms exist, and the singular expression of these MHC isoforms in muscle fibers forms the basis for histochemical classification of different fiber types (18,24,25,31). In the neonatal rat Dia m , a neonatal isoform of MHC (MHC Neo ) is predominantly expressed, most often in combination with MHC Slow or MHC 2A isoforms (10,16,18,30,33). During the first 3-4 postnatal weeks, a dramatic transition in MHC isoform expression occurs in the rat Dia m , with the complete disappearance of MHC Neo expression by ϳ28 days of age (D-28).…”
mentioning
confidence: 99%